2013
DOI: 10.1186/1742-4755-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Women’s well-being and reproductive health in Indian mining community: need for empowerment

Abstract: This paper is a qualitative study of women’s well-being and reproductive health status among married women in mining communities in India. An exploratory qualitative research design was conducted using purposive sampling among 40 selected married women in a rural Indian mining community. Ethical permission was obtained from Goa University. A semi-structured indepth interview guide was used to gather women’s experiences and perceptions regarding well-being and reproductive health in 2010. These interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
(40 reference statements)
3
29
0
Order By: Relevance
“…The results likewise demonstrated that problems in the relationship between men and women are associated with women's empowerment in decision making about reproduction. As discovered by D'Souza et al [17], marital relations influence reproductive decision making, and women's poor health and relations with their spouses lead to low-quality marriages. Hindin [48] found a significant relationship between women's reproductive health and the involvement of men in this issue; encouraging them to participate in resolving reproductive problems is an important strategy for empowering women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results likewise demonstrated that problems in the relationship between men and women are associated with women's empowerment in decision making about reproduction. As discovered by D'Souza et al [17], marital relations influence reproductive decision making, and women's poor health and relations with their spouses lead to low-quality marriages. Hindin [48] found a significant relationship between women's reproductive health and the involvement of men in this issue; encouraging them to participate in resolving reproductive problems is an important strategy for empowering women.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, women do not use contraceptives given the lack of or weak support from spouses or communities [16]. Their empowerment in this regard is also particularly influenced by their ability to communicate with their spouses [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While for rural women, culture, body politics and stigma become challenges that contribute to the impediment of reproductive health for them [3]. In India [4], the reproductive years for women are of central importance to their lives. Women's role in reproductive health is affected by, and could influence her status and empowerment as an individual.…”
Section: Introductionmentioning
confidence: 99%
“…Women's role in reproductive health is affected by, and could influence her status and empowerment as an individual. However, particularly in the rural communities, Indian women have a subordinate position compare to men and have less power, autonomy status and independence [4]. So, from the various studies, women, especially young women still must face a lot of boundaries related to health reproductive.…”
Section: Introductionmentioning
confidence: 99%